Geographical miss of the prostate during image‐guided radiotherapy with a 6‐mm posterior expansion margin. Issue 2 (8th November 2016) - Oates, Richard; Jones, Daryl; Foroudi, Farshad; Gill, Suki; Ramachandran, Prabhakar; Schneider, Michal; Lim Joon, Michael; Kron, Tomas
Abstract: Introduction: Our department commonly uses a planning target volume (PTV) expansion of 6 mm posterior and 1 cm in all other directions when treating prostate cancer patients with image‐guided radiotherapy (IGRT). This study aimed to test the adequacy of this PTV expansion by assessing geographical miss of the prostate on post‐treatment cone‐beam CT (CBCT) and identify those at risk of geographical miss. Methods: Twenty‐two prostate cancer patients receiving IGRT with implanted fiducial markers underwent daily pre‐treatment orthogonal kV imaging followed by a post‐treatment CBCT for a total of 432 fractions. The prostate was outlined on all CBCTs. For each imaging set, the volume of geographic miss was measured by subtracting the PTV from the planning CT and prostate volume on the post‐treatment CBCT. Results: The prostate volume moved outside the PTV by >0.01 cc in 9% of fractions (39/432). This occurred in 13 (59%) of 22 patients. Large prostates >40 cc and >50 cc had significantly more geographical miss events (both P < 0.001). Changes in rectal filling appear to be responsible for prostate motion/deformation in 82% (32/39) of fractions. Conclusions: Our analysis suggests that, despite IGRT, prostate PTV margins are not adequate in some patients, particularly those with large prostates. PTV margins may be reduced in some other patients. Prostate rotation and deformation play an important role in setting margins and may not always be represented accurately by fiducial marker displacements. Individualised and adaptive margins for prostate cancer patients should be a priority for future research. Abstract : This study identified that a posterior planning target volume margin of 6 mm may not be adequate for all prostate radiotherapy patients. Changes in rectal filling appeared to be responsible for most geographical misses of the prostate. Patients with a large prostate appear to be 'at risk' of prostate geographical miss.